An ultrasonic measurement method for full range of oil film thickness. (March 2019) - Zhang, Kai; Dou, Pan; Wu, Tonghai; Feng, Kai; Zhu, Youquan
Ultrasonic method is quite promising for oil film thickness measurement in industry, while there is normally a dead zone for one ultrasonic sensor with a special center frequency when measuring the oil film thickness by the traditional reflection coefficient amplitude. In this paper, an ultrasonic measurement method for full range of oil film thickness was investigated. The theoretical relationship between the oil film thickness and the reflection coefficient phase was firstly built up and the reflection coefficient phase was found to be able to measure the oil film thickness in the dead zone. Then the reflection coefficient amplitude and phase were combined to measure the oil film thickness in the full range. A high-precision calibrated rig, which could form a series of known film thicknesses oil layers, was set up and the performance of this method was shown to work well. This method is significant for online oil film thickness monitoring in industry.